«One as all». Mental foundations of solidarity action (Actual Problems of Mind, 2023)
Analyzing the problem of the «semantics of action», M. V. Popovych gave an anecdotal example, according to which in a dialogue between two competitors (traveling salesmen) who suspect each other of deception in advance, one of them, convinced that the opponent will not believe him anyway, decides to tell him the truth, thus «confounding his cards». Taking the competitor's information as true, the opponent, at the same time, makes it clear to the opponent that, despite his words, he fully understood his real intention -- to mislead him. In addition to the story about these «like-minded» competitors, the proposed publication cites other cases of understanding each other without words, albeit non-antagonistic. This is an old married couple, according to O. Spengler, and the original team, according to O. M. Freudenberg. In both examples the so-called «We» stands out very clearly, for which thoughts on a certain occasion are common, without the need for prior agreement. Accordingly, the article draws attention to an interesting, from the point of view of the philosophy of action, phenomenon, which the author repeatedly observed in the student group during his studies at Kyiv University named after T.G. Shevchenko (1980-85). According to him, a group of people (students) reacts to a certain challenge as a «collective individual» --  «all as one», or the same «We». There is a peculiar phenomenon of an instant solidarity protest reaction to some challenge, as a result of a «conspiracy without language», which is based on certain worldview markers of acceptable and unacceptable and reveals a structure in the form of a series of step-by-step actions that characterizes equanimity (mental measurement). This manifestation of «We» is opposed to two other, more traditional, manifestations of this category -- a mechanical «we», united by a common language or belonging to the same reference group, but not devoid of internal contradictions (the example of traveling salesmen, according to M.V. Popovich), and -- «we» of the totalitarian society, formed by the opaque way of hypnosis, deception (propaganda), violence by the leader-«puppet master». The latter can be characterized as «we are the victims». In a free society, priority is given to the authenticity and value of the unintended, spontaneous expression of «We», which opposes the phantom power of an illegitimate leader.
Keywords: All as one; We; mentality; intention; solidarity action; studentship